Utilization of CO2-Available Organocatalysts for Reactions with Industrially Important Epoxides - Weidlich, Tomáš; Kamenická, Barbora (My University, 2022)
Recent knowledge in chemistry has enabled the material utilization of greenhouse gas (CO2) for the production of organic carbonates using mild reaction conditions. Organic carbonates, especially cyclic carbonates, are applicable as green solvents, electrolytes in batteries, feedstock for fine chemicals and monomers for polycarbonate production. This review summarizes new developments in the ring opening of epoxides with subsequent CO2-based formation of cyclic carbonates. The review highlights recent and major developments for sustainable CO2 conversion from 2000 to the end of 2021 abstracted by Web of Science. The syntheses of epoxides, especially from bio-based raw materials, will be summarized, such as the types of raw material (vegetable oils or their esters) and the reaction conditions. The aim of this review is also to summarize and to compare the types of homogeneous non-metallic catalysts. The three reaction mechanisms for cyclic carbonate formation are presented, namely activation of the epoxide ring, CO2 activation and dual activation.
Využití dostupných organokatalyzátorů pro reakce CO2 s průmyslově významnými epoxidy
Keywords: cycloaddition; ionic liquid; deep eutectic solvents; onium salt; homogeneous catalysts; cykloadice; ionotvé kapaliny; eutektická rozpouštědla; oniová sůl; homogenní katalyzátory